The Impact of Household Economic Deterioration Caused by the COVID-19 Pandemic and Socioeconomic Status on Suicidal Behaviors in Adolescents: A Cross-sectional Study Using 2020 Korea Youth Risk Behavior Web-based Survey Data - Sanggu Kang; Yeri Jeong; Eun Hye Park; Seung-sik Hwang (Korean Society for Preventive Medicine, 2022)
Objectives Economic hardship has a serious impact on adolescents' mental health. The financial impact of the coronavirus disease 2019 (COVID-19) pandemic was more severe for low-income families, and this also impacted adolescents. This study aimed to examine the associations of economic deterioration (ED) caused by the COVID-19 pandemic and low socioeconomic status (SES) with adolescents' suicidal behaviors. Methods This study analyzed data from the 2020 Korea Youth Risk Behavior Web-based Survey, which included 54 948 middle and high school students. Odds ratios (ORs) of suicidal ideation, suicidal planning, and suicide attempts related to ED and SES were calculated using multivariable logistic regression. We calculated relative excess risks due to interaction to assess additive interactions. Results The ORs for suicidal ideation, suicidal planning, and suicide attempts related to combined severe ED and low SES were 3.64 (95% confidence interval [CI], 3.13 to 4.23), 3.88 (95% CI, 3.09 to 4.88), and 4.27 (95% CI, 3.21 to 5.69), respectively. Conclusions ED and low SES were significantly associated with suicidal behaviors in adolescents. Although no significant additive interaction was found, the ORs related to suicidal ideation, suicidal planning, and suicide attempts were highest among adolescents from low-income families with severe ED. Special attention is needed for this group, considering the increased impact of economic inequality due to the COVID-19 pandemic.